2008
DOI: 10.1080/00288330809509955
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance of cyanotoxin production by cryopreserved cyanobacteria in the New Zealand culture collection

Abstract: A culture collection of freshwater planktonic and benthic cyanobacteria collected from sites across New Zealand has been established at the Cawthron Institute, Nelson, New Zealand. Limited resources led to uncertainty regarding the longterm maintenance of this collection. The present study demonstrates cryopreservation to be a viable method for long-term storage of cyanobacteria. Seventeen of 20 strains evaluated were successfully cryopreserved using the permeating cryopreservation agent dimethyl sulfoxide (Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 14 publications
1
22
0
Order By: Relevance
“…CAWBG-16, isolated in New Zealand, produces primarily desmethylmicrocystin-LR (Wood et al 2008). Initial salinity experiments demonstrated that CAWBG16 could survive (but not undergo division) in seawater of 30 ppt (data not shown).…”
Section: Detection Of Microcystins In Pacific Oysters Using Elisamentioning
confidence: 87%
See 1 more Smart Citation
“…CAWBG-16, isolated in New Zealand, produces primarily desmethylmicrocystin-LR (Wood et al 2008). Initial salinity experiments demonstrated that CAWBG16 could survive (but not undergo division) in seawater of 30 ppt (data not shown).…”
Section: Detection Of Microcystins In Pacific Oysters Using Elisamentioning
confidence: 87%
“…Strains were cryopreserved under liquid nitrogen as described in Rhodes et al (2006) and Wood et al (2008). These cultures are now maintained in a cryobank at the Cawthron Institute Culture Collection of Microalgae (CICCM; http://cultures.caw thron.org.nz/).…”
Section: Cryopreservation Of Isolatesmentioning
confidence: 99%
“…Whilst for some cyanobacteria, lyophilization is an alternative option to cryogenic storage Silva, Ferrari, and Silva, 2007), preservation in liquid nitrogen should be the preferred approach. This is because the stability of production of primary and secondary metabolites has been confirmed after ultralow-temperature storage (Hédoin et al, 2006;Wood et al, 2008), whereas, although there are no data for cyanobacteria, production losses of secondary metabolites have been reported in suboptimally lyophilized fungi (Ryan et al, 2003).…”
Section: Cryopreserving Biological Resourcesmentioning
confidence: 96%
“…Over 250 of these strains are held cryopreserved in liquid nitrogen. The collection includes a number of unique species and strains and underpins applied and fundamental research including: characterisation of algal toxin producers and their toxins, phytoplankton monitoring, validation of molecular-based detection tools, as well as research for bioactive and novel compounds (Rhodes et al, 2006; Woods et al, 2008). …”
Section: Cryobanking Worldwidementioning
confidence: 99%